2022
DOI: 10.1021/acschembio.2c00727
|View full text |Cite
|
Sign up to set email alerts
|

Widespread, Reversible Cysteine Modification by Methylglyoxal Regulates Metabolic Enzyme Function

Abstract: Methylglyoxal (MGO), a reactive metabolite byproduct of glucose metabolism, is known to form a variety of posttranslational modifications (PTMs) on nucleophilic amino acids. For example, cysteine, the most nucleophilic proteinogenic amino acid, forms reversible hemithioacetal and stable mercaptomethylimidazole adducts with MGO. The high reactivity of cysteine toward MGO and the rate of formation of such modifications provide the opportunity for mechanisms by which proteins and pathways might rapidly sense and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
1
5
1
Order By: Relevance
“…GAPDH is a moonlighting protein with many cellular functions including glycolysis and regulation of cell survival and apoptosis . In previous studies, GAPDH has been reported to be susceptible to modification by MGO at its catalytic Cys residue and additional Arg and Lys sites, which can inhibit its enzymatic function. Our mass spectrometry results confirmed that MGO covalently modifies GAPDH at multiple Lys and Arg residues (Table S3 and Figures S8–14). Importantly, GAPDH has been reported to bind telomeric DNA sequences with a K d of 45 nM .…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…GAPDH is a moonlighting protein with many cellular functions including glycolysis and regulation of cell survival and apoptosis . In previous studies, GAPDH has been reported to be susceptible to modification by MGO at its catalytic Cys residue and additional Arg and Lys sites, which can inhibit its enzymatic function. Our mass spectrometry results confirmed that MGO covalently modifies GAPDH at multiple Lys and Arg residues (Table S3 and Figures S8–14). Importantly, GAPDH has been reported to bind telomeric DNA sequences with a K d of 45 nM .…”
Section: Resultssupporting
confidence: 76%
“…It should be noted that MGO is known to covalently modify GAPDH, leading to enzymatic inhibition and alteration in isoelectric point. 81,82,84 In neural precursor cells (NPCs), it was found that MGO modification of GAPDH impacted Notch signaling which affected NPC homeostasis. 104 MGOinduced GAPDH−DNA cross-linking may play an additional role in the association between MGO and aging processes linked to telomeres; however, more detailed studies are needed to clarify this hypothesis.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B and table S1). In contrast to the conventional view of FA as an indiscriminate electrophile, the data revealed privileged FA-sensitive cysteine sites, similar to other reactive species such as hydrogen peroxide, nitric oxide, and methylglyoxal ( 27 , 28 ), and provides foundational information on FA-cysteine reactivity across the proteome in a systematic manner. Notably, modified cysteines were found enriched in protein families spanning FA-dependent pathways (e.g., carbon metabolism and glutathione) and one-carbon metabolism (e.g., one-carbon amino acids and folate) rather than demonstrating proteome-wide, indiscriminate reactivity (Fig.…”
Section: Resultscontrasting
confidence: 55%
“…Methylglyoxal (MGO) is a highly reactive metabolite produced by the degradation of the triose phosphates glyceraldehyde phosphate (GAP) and dihydroxyacetone phosphate (DHAP), which interconvert within glycolysis through the enzyme triosephosphate isomerase. MGO can chemically modify a variety of nucleophilic biomolecules including proteins, nucleic acids, and even metabolites. The abundance of MGO-modified proteins has been associated with a number of diseases including diabetes, cancer, neurodegeneration, and aging, with Parkinson’s disease-specific connections potentially being explained by a role for DJ-1 in protecting against accumulation of glycated α-synuclein. , MGO is principally detoxified by the glyoxalase system, which consists of the enzymes GLO1 and GLO2. MGO reacts with reduced glutathione (GSH) to form a reversible hemithioacetal, which can be converted to lactoyl glutathione (Lac-GSH) by Zn 2+ metalloenzyme GLO1 . GLO2 then may hydrolyze Lac-GSH to recycle the GSH and produce d -lactate …”
Section: Introductionmentioning
confidence: 99%